1992
DOI: 10.1016/0014-5793(92)81202-w
|View full text |Cite
|
Sign up to set email alerts
|

Interrelations of M‐intermediates in bacteriorhodopsin photocycle

Abstract: The photocycles of the wild-type bacteriorhodopsin and the D96N mutant were investigated by tile flash-photolysis technique. Tile M-intermediate formation (400 nm) and the L-intermediate decay (520 nm) were found to be well described by a sum of two exponents (time constants, rt = 65 and r, = 250/~s) for the wild-type bR and thr~ exponents (r~ = 55 ,us, r,. = 220 as and r.a = 1 ms) for the D96N mutant of bR. A component with r = 1 ms was found to be prescott in the photoeycle of the wild-type bacteriorhodopsin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

1993
1993
1996
1996

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 7 publications
3
37
0
Order By: Relevance
“…It has been known for some time that there are (at least) two forms of the M intermediate in the bacteriorhodopsin (BR) photocycle, one (Mf) with faster kinetics than the other (Ms), and that the level of actinic light alters the fractions of these two species (see [2][3][4] and references therein). More recently, it has been shown that Mf decays to the ground state through the O intermediate whereas Ms does not [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…It has been known for some time that there are (at least) two forms of the M intermediate in the bacteriorhodopsin (BR) photocycle, one (Mf) with faster kinetics than the other (Ms), and that the level of actinic light alters the fractions of these two species (see [2][3][4] and references therein). More recently, it has been shown that Mf decays to the ground state through the O intermediate whereas Ms does not [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The mutant D96N gives this opportunity owing to an ability of a number of weak acids (azide, cyanate, nitrite, etc.) to serve as proton donors for the Shiffbase [10][11][12][13][14][15]. The proportional dependence of the rate of the M decay on the concentration of the protonated form of azide indicates that it is a second-order reaction.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known now that the M intermediate, in fact, comprises a set of different forms with similar absorption spectra [4][5][6][7][8][9]. There are many pieces of evidence for protein conformational changes accompanying the proton transport, especially the reprotonation of the Schiff base by the internal proton donor D96, i.e.…”
Section: Introduction 3 Resultsmentioning
confidence: 99%
“…the decay of the M intermediate [9][10][11][12][13][14]. The mutation leading to the lack of proton donor (D96N) causes a dramatic retardation of the M decay [15,16], and this kinetic defect can be repaired by azide and other anions of small weak acids [7,[17][18][19][20][21][22]. It was initially supposed that the action of azide was associated with its ability to serve as the penetrating proton donor [7,[17][18][19][20][21], however, another model has recently been put forward [22] according to which the tightly bound anionic form of azide can catalyze proton transfer to the Schiff base.…”
Section: Introduction 3 Resultsmentioning
confidence: 99%
See 1 more Smart Citation